2021
DOI: 10.3390/nu13072212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sarcopenia on Acute Kidney Injury after Infrarenal Abdominal Aortic Aneurysm Surgery: A Propensity Matching Analysis

Abstract: Background: Sarcopenia contributes to increased morbidity and mortality in patients undergoing surgery for abdominal aortic aneurysms (AAA). However, few reports have demonstrated whether sarcopenia would affect the development of postoperative acute kidney injury (AKI) in these patients. This study aimed to examine whether sarcopenia is associated with AKI and morbidity and mortality after infrarenal AAA operation. Methods: We retrospectively analysed 379 patients who underwent infrarenal AAA surgery. The dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Eight articles were excluded and the remaining fifteen studies were found to be eligible for this meta-analysis. [13][14][15][16][18][19][20][23][24][25][26][27][28][29][30] The majority of the studies were retrospective cohort in nature ( There was wide variation in the studies in defining low skeletal muscle mass. All studies measured defined skeletal muscle area by measuring the bilateral psoas muscles with or without additional muscular structures.…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles were excluded and the remaining fifteen studies were found to be eligible for this meta-analysis. [13][14][15][16][18][19][20][23][24][25][26][27][28][29][30] The majority of the studies were retrospective cohort in nature ( There was wide variation in the studies in defining low skeletal muscle mass. All studies measured defined skeletal muscle area by measuring the bilateral psoas muscles with or without additional muscular structures.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that sarcopenia is associated with kidney damage and decreased estimated glomerular filtration rate 21,22 . Another study demonstrated that sarcopenia is associated with increased postoperative AKI incidence in infrarenal abdominal aortic aneurysms operation 23 …”
Section: Introductionmentioning
confidence: 93%
“…21,22 Another study demonstrated that sarcopenia is associated with increased postoperative AKI incidence in infrarenal abdominal aortic aneurysms operation. 23 However, there are no studies on the association between donor sarcopenia and postoperative surgical outcomes in donors undergoing hepatectomy for LT. Therefore, in this study, we evaluated the association between donor sarcopenia and the development of postoperative AKI after donor hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sarcopenia—musculoskeletal loss was associated with AKI occurrence after AAA repair—is known to be an independent mortality factor following AAA therapy. According to studies [ 9 , 10 ] PC-AKI is the third most common reason for hospital-acquired acute renal failure and is linked to a high mortality rate. Due to this, a number of methods (such as pre and posthydration and the injection of N-acetylcysteine) have been shown to be somewhat useful in preventing CIN [ 11 ], but they are not always practical, particularly when treating patients who have suffered serious injuries.…”
Section: Introductionmentioning
confidence: 99%